The Influence Of Perceived Risk, Perceived Ease Of Use And Perceived Usefulness On The Decision To Use The Application Seabank For Generation Z In Surabaya - Amini, Lia Nurhalijah; Aminah, Siti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The advancement of technology that is growing rapidly at this time is very helpful for people in various activities, one of which is in terms of transactions both for shopping and paying for daily needs. the purpose of this study was to determine how the effect of perceived risk, perceived convenience and perceived benefits on one's usage decision in using the seabank application. the respondents of this study were generation z in Surabaya. This research uses a quantitative approach, with a sample size of 90 respondents. Using purposive sampling method to collect samples. The data analysis technique used is Partial Least Square (PLS) based on Structural Equation Modeling (SEM). Based on the results of the study, it shows that usage decisions are positively and significantly influenced by perceived risk and perceived benefits, while perceived convenience has a positive but insignificant effect.